2022
DOI: 10.1093/jjco/hyab215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GLIM-defined malnutrition on postoperative clinical outcomes in patients with colorectal cancer

Abstract: Background Malnutrition is common in colorectal cancer patients. Malnutrition is recognized as a risk factor for adverse postoperative outcomes, yet there are no consistent diagnostic criteria for it. Thus, the Global Leadership Initiative on Malnutrition published new universal criteria. We aimed to investigate the prevalence of malnutrition with the application of Global Leadership Initiative on Malnutrition criteria, and explore the correlations between Global Leadership Initiative on Maln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…According to previous studies, the prevalence of malnutrition in the gastrointestinal is about 30–50% ( 11 13 ). According to GLIM criteria, the prevalence of malnutrition was 28.27% in our study which is also consistent with previous studies ( 14 16 ). For the reason why our study population had a relatively lower incidence of malnutrition, we hypothesized that it might be due to the higher incidence of colorectal cancer and the almost lack of stage IV cancer patients in our study.…”
Section: Discussionsupporting
confidence: 93%
“…According to previous studies, the prevalence of malnutrition in the gastrointestinal is about 30–50% ( 11 13 ). According to GLIM criteria, the prevalence of malnutrition was 28.27% in our study which is also consistent with previous studies ( 14 16 ). For the reason why our study population had a relatively lower incidence of malnutrition, we hypothesized that it might be due to the higher incidence of colorectal cancer and the almost lack of stage IV cancer patients in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the prevalence of GLIM-defined malnutrition was 24.8%, and other nutritional tools classified 31.0-46.9% of patients with rectal cancer as malnourished. Recently, Song et al (3) reported that the prevalence of GLIM-defined malnutrition was 23.6% in patients with colorectal cancer, which is similar to the prevalence of GLIM-defined malnutrition in this study. Many previous studies have demonstrated that malnutrition is both a short and long-term risk factor.…”
Section: Discussionsupporting
confidence: 89%
“…In 2020, an estimated 1.9 million cases and 935,000 deaths will be attributed to colorectal cancer (including anal cancer), representing approximately one in 10 cancer cases and deaths ( 1 ). Patients with cancer often experience malnutrition, which is related with increased postoperative complications and mortality ( 2 , 3 ). Thus, the nutritional status of patients with cancer should be assessed, and nutritional interventions should be provided as necessary in the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…SGA has been used previously in patients with colorectal cancer, finding a prevalence between 35 and 40% [ 11 , 30 ]. A Japanese study found a prevalence of preoperative malnutrition of 23.6%, which was associated with postoperative complications, overall survival, and disease-free survival in colorectal cancer patients after radical resection surgery [ 31 ]. These findings were also corroborated by the results from a large population database from the United States [ 32 ].…”
Section: Discussionmentioning
confidence: 99%